The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1590/0103-8478cr20150989
|View full text |Cite
|
Sign up to set email alerts
|

Gender on the growth of Criollo foals from birth to three years of age

Abstract: The objective of the present study was to evaluate the effect of gender on the growth of Criollo foals, in order to use this information as a reference for breeding as well as in future research. Body height, thoracic perimeter, and cannon bone perimeter of 75 foals were measured from two farms in Rio Grande do Sul, Brazil (Lat. 32°, 33′, 58″, Long. 53°, 22′, 33″)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
(10 reference statements)
2
8
0
2
Order By: Relevance
“…Mota et al (2010) also concluded that males are generally taller than females. These differences between both sexes can be explained by sexual dimorphism: in males, secondary sexual characteristics influence the growth of tissues and, consequently, of body regions, which leads to differences in growth patterns related to height (Pimentel et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mota et al (2010) also concluded that males are generally taller than females. These differences between both sexes can be explained by sexual dimorphism: in males, secondary sexual characteristics influence the growth of tissues and, consequently, of body regions, which leads to differences in growth patterns related to height (Pimentel et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Since the breed's inception less than 200 years ago, its biotype has become more athletic, with higher quality morpho-functional features for a saddle horse (Casiuch, 2016). In this context, several studies have evaluated the growth characteristics of the horses of this breed (Souza et al, 2017;Ribeiro et al, 2018); however, few of them take into account morphometric variables, such as body length and thoracic and cannon perimeters, in statistical modeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum measurement required for registry confirmation is 18 cm for males and 17 cm for females. Pimentel et al (2017) evaluated Criollo colts from birth to three years of age and found that males reached the minimum requirement for registration at 18 months of age, while females reached the minimum requirement for registration, on average, at 11 months of age. Males presented greater cannon bone circumferences.…”
Section: Discussionmentioning
confidence: 99%
“…CARROL & HUNTINGTON (1988) reported that horses' height at withers (r=0.75) and body length (r=0.62) were highly correlated with body weight, demonstrating the influence of morphometric variables on equine body development. At birth, a foal's height at withers is estimated to correspond to approximately 60% of the adult height and, at the end of its first year of life, to approximately 90% of the adult height (GREEN, 1969;GARCIA et al 2011;PIMENTEL et al, 2017).…”
Section: Introductionmentioning
confidence: 99%